Comparison of turbulence models for flow past NACA0015 airfoil using OpenFOAM - Chakrit Suvanjumrat (2018)
© 2017, Chulalongkorn University 1. All rights reserved. The open source code software, OpenFOAM, was applied for simulating flow past NACA0015 airfoil. Three economical turbulence models for aerospace applications were selected comprising Spalart-Allmaras model, Wilcox k - ω model and Menter SST k - ω model, respectively. The non-dimension y+was used to analyze the near-wall flow. The C-type domain for airfoil simulation was considered for an appropriate dimension to protect the effect of boundary conditions. The zero pressure gradient problem of the pressure-velocity coupling was used an effective algorithm, SIMPLE, for solving. The central differencing, upwind differencing, and linear upwind differencing (LUD) scheme were used to solve the convection-diffusion equation of the flow past airfoil. The simulation results included lift coefficient (CL) and drag coefficient (CD) were obtained from this computational fluid dynamics (CFD) method. The turbulence models had been validated to the physical experiment. The wind tunnel was set up to test the flow past NACA0015 airfoil. The Reynolds number (Re) at 160,000 and 360,000 were controlled in order that the NACA0015 airfoil with the large range angle of attack from 0 to 20 degrees was immersed in the low wind speeds and turbulent flow. The suitable turbulence model was the Menter SST k - ω model which employed SIMPLE algorithm and LUD scheme for solving. These CFD results lower the stall angle of attack had the average errors of CLand CDwith were less than 13.15% and 22.36%, respectively.